GREEN FINANCE: UNLOCKING THE POTENTIAL OF SUSTAINABLE INVESTMENT FOR FUTURE BUSINESS GROWTH - Hasanuddin, Hasanudin; Rimbano, Dheo; Nuraini, Ani; Kuswandi, Dadi; Makkulau, Andi Runis (UIN Sunan Gunung Djati Bandung, 2024)
Climate change has become one of the greatest challenges of this century, affecting global economic stability as well as business performance and growth. Green investments are needed to mitigate these negative impacts, integrating sustainability into business operations which in turn can benefit companies in the long term. Green finance is key to ensuring sustainable business growth and effective handling of environmental issues. This research aims to examine how environmentally friendly finance can support sustainable growth and its impact on the global economy. The research method used is a descriptive qualitative approach, relying on data from previous studies that are relevant to the topic. Data processing through thematic analysis aims to identify patterns and gain in-depth insight into the implementation and impact of environmentally friendly finance. The research results show that the implementation of environmentally friendly finance is essential for long-term economic stability and growth. Sustainability-oriented investments improve a company's reputation, attract investors, and support financial stability. However, there are significant challenges in its implementation related to internal resistance and regulatory barriers. Effective strategies involve cooperation between governments and international institutions to create supportive incentives and frameworks. Education and training for players in the financial sector are also critical to increasing understanding and skills in environmentally friendly financial applications.